Crosstalk Between Immune Cell and Oncolytic Vaccinia Therapy Enhances Tumor Trafficking and Antitumor Effects - Sampath, Padma (Nature Publishing Group, 2013)
The combination of an oncolytic virus, that directly destroys tumor cells and mediates an acute immune response, with an immune cell therapy, capable of further enlisting and enhancing the host immune response, has the potential to create a potent therapeutic effect. We have previously developed several strategies for optimizing the delivery of oncolytic vaccinia virus vectors to their tumor targets, including the use of immune cell-based carrier vehicles and the incorporation of mutations that increase production of the enveloped form of vaccinia (extracellular enveloped viral (EEV)) that is better adapted to spread within a host. Here, we initially combine these approaches to create a novel therapeutic, consisting of an immune cell (cytokine-induced killer, CIK) preloaded with an oncolytic virus that is EEV enhanced. This resulted in direct interaction between the viral and immune cell components with each assisting the other in directing the therapy to the tumor and so enhancing the antitumor effects. This effect could be further improved through CCL5 expression from the virus. The resulting multicomponent therapy displays the ability for synergistic crosstalk between components, so significantly enhancing tumor trafficking and antitumor effects.